Studi Literatur Tentang Pentingnya Penerapan Manajemen Risiko Dalam Industri Jaminan Pasca-Covid-19: Literature Study on the Importance of the Implementation of Risk Management in the Post-COVID-19 Guarantee Industry - Arifin, Antoni Ludfi; Latunreng, Wahyuddin; Azmy, Ahmad (Anterior Jurnal, 2025)
The guarantee business is a risky business, where the recipient of the guarantee (bank) transfers the debtor's credit risk to the guarantee company. Guarantee companies have been burdened with lousy credit claims and layoff claims since March 2020, following the emergence of the COVID-19 pandemic. Guarantee companies need to manage risk well so that the transfer of this risk can be an advantage in the form of a guarantee fee (IJP) and profit. The research is qualitative research through a review of relevant literature published in 2010-2021. Researchers seek to understand the implementation of risk management that has been carried out, especially in the non-bank financial industry. The study results show that the insurance company needs to prepare to implement risk management and risk mitigation. It can be done by preparing internal SOPs, reinsurance, co-guaranteeing, and subrogating the post-COVID-19 pandemic. Guarantee companies need to identify risks, measure risks, and then accept, reject, mitigate, or transfer risks. It can be done by implementing embedded enterprise risk management (ERM) in enterprise business processes.